2014
DOI: 10.1080/13676261.2014.918246
|View full text |Cite
|
Sign up to set email alerts
|

Family contexts and adolescents' emotional status

Abstract: Children's living arrangements have become increasingly diverse and complex in recent decades: a significant proportion of children reside in stepfamilies or in separated one-parent families, even in countries such as Italy, which only recently are undergoing a transition from traditional to less traditional family behaviours. The present study explores whether adolescents living in families which are the result of separation or divorce have lower levels of psychological well-being than those living in more tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 89 publications
0
8
0
Order By: Relevance
“…Many deaths were caused by the COVID-19 virus globally [17]. This virus is easily transmitted within close distance or physical contact [2]. It strikes humans and causing respiratory and digestive tract diseases with varied severity degrees [3].…”
Section: Internal Factors Of Learning Anxietymentioning
confidence: 99%
See 1 more Smart Citation
“…Many deaths were caused by the COVID-19 virus globally [17]. This virus is easily transmitted within close distance or physical contact [2]. It strikes humans and causing respiratory and digestive tract diseases with varied severity degrees [3].…”
Section: Internal Factors Of Learning Anxietymentioning
confidence: 99%
“…COVID-19 virus was first reported in Wuhan, China, and spread worldwide in March 2020 [1]. COVID-19 is easily transmitted from a close distance or physical contact [2]. COVID-19 strikes humans to cause respiratory and digestive tract diseases with varied severity degrees [3].…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of an assumption that non-resident father involvement improves adolescent adjustment, the researchers found that levels of adolescent well-being cause non-resident father involvement or lack of involvement rather than an adolescent's well-being resulting from resulting from non-resident father involvement or lack thereof. Meggiolaro & Ongaro (2014) examined family contexts and adolescent's emotional status. The researchers focused on stepfamilies and regarded them as an institution that was incomplete and argued that step-parents face ambiguous parental roles and norms which resulted in less effective parenting.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, the influence of a family’s socioeconomic status, its functioning, and the parent’s behaviors and psycho-physical well-being are not well researched in Italy. It should be studied in-depth, distinguishing the effects of the family structure according to the specific behaviors and well-being aspects of the adolescent [ 59 ].…”
Section: Introductionmentioning
confidence: 99%